2021
DOI: 10.31557/apjcc.2021.6.3.271-276
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Nigerian Healthcare Providers Competence in Breast Cancer Clinical Pathway Development using Blended Learning Approach

Abstract: Purpose: Clinical pathways are a means of translating universal clinical guidelines into local protocols to inform clinical practice. This study aimed to evaluate the effectiveness of using a blended learning approach for providing instruction and building competency on the development of breast cancer clinical pathways, using the guidelines from the National Cancer Control Network (NCCN). Methods: A one-group pretest-post test design was used for this study. Participants included healthcare providers and stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Improvements can be made through the provision of periodic training to improve the process and quality of patient documentation outcomes (Mater and Ibrahim, 2014). A study in Nigeria reported that the blended learning approach was quite effective in increasing the knowledge and competence of each healthcare professional on clinical pathways (Eguzo et al, 2021). The results of the quality assessment of dimension 1 show that the clinical pathway documentation is still not optimal.…”
Section: Content and Quality Evaluationmentioning
confidence: 99%
“…Improvements can be made through the provision of periodic training to improve the process and quality of patient documentation outcomes (Mater and Ibrahim, 2014). A study in Nigeria reported that the blended learning approach was quite effective in increasing the knowledge and competence of each healthcare professional on clinical pathways (Eguzo et al, 2021). The results of the quality assessment of dimension 1 show that the clinical pathway documentation is still not optimal.…”
Section: Content and Quality Evaluationmentioning
confidence: 99%